Anr, the anaerobic global regulator, modulates the redox state and oxidative stress resistance in Pseudomonas extremaustralis - Tribelli, Paula Maria (2013)
The role of Anr in oxidative stress resistance was investigated in Pseudomonas extremaustralis, a polyhydroxybutyrate-producing Antarctic bacterium. The absence of Anr caused increased sensitivity to hydrogen peroxide under low oxygen tension. This phenomenon was associated with a decrease in the redox ratio, higher oxygen consumption and higher reactive oxygen species production. Physiological responses of the mutant to the oxidized state included an increase in NADP(H) content, catalase activity and exopolysaccharide production. The wild-type strain showed a sharp decrease in the reduced thiol pool when exposed to hydrogen peroxide, not observed in the mutant strain. In silico analysis of the genome sequence of P. extremaustralis revealed putative Anr binding sites upstream from genes related to oxidative stress. Genes encoding several chaperones and cold shock proteins, a glutathione synthase, a sulfate transporter and a thiol peroxidase were identified as potential targets for Anr regulation. Our results suggest a novel role for Anr in oxidative stress resistance and in redox balance maintenance under conditions of restricted oxygen supply.